Sains Sebagai Perluasan dari Islam - Nasri Nasri (Pendidikan Agama Islam STIT Palapa Nusantara, 2019)
Islam is a religion based on submission (Taslim) towards the will of God Almighty, Allah SWT. And based on the knowledge of His oneness. Islam is the last religion. The prophet of Islam is Khatam Al-Anbiya (Closing of the Prophets) and fourteen centuries of human history have recognized the validity of Islam as the last religion. The relationship between the Qur'an and science is a priori surprising, especially if it becomes a harmony and not a contradiction. The confrontation between religious books and scullary ideas proclaimed by science, perhaps in the eyes of people is now a paradox.